1983
DOI: 10.1021/ac00259a018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single- and dual-beam configurations for thermal lens spectrometry

Abstract: NaCl were used as samples for the nebulizer/heat chamber. Evidently, small salt crystals were formed from the water droplets passing through the heat chamber. Since the detection limits agree, we conclude the salt crystals were completely vaporized inside the spark and did not significantly alter the nature of the plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Since its development by Whinnery (1)(2)(3)(4)(5), thermal lens techniques have been recognized as useful in the analysis of weakly absorbing species (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Specifically, the technique has been considered as a detector for chromatography and flow injection analysis (17)(18)(19)(20)(21)(22).…”
Section: Time-resolved Thermal Lens Measurements In Flowing Samplesmentioning
confidence: 99%
“…Since its development by Whinnery (1)(2)(3)(4)(5), thermal lens techniques have been recognized as useful in the analysis of weakly absorbing species (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Specifically, the technique has been considered as a detector for chromatography and flow injection analysis (17)(18)(19)(20)(21)(22).…”
Section: Time-resolved Thermal Lens Measurements In Flowing Samplesmentioning
confidence: 99%
“…In particular, it has been applied to the measurement of absorbances and of the concentration of chemical species in liquids [48,49] or in gases [50,51]. These gradients are optically equivalent to a diverging lens, called a thermal lens, leading to an enhancement of the beam divergence.…”
Section: Thermal Bloomingmentioning
confidence: 99%
“…Careful comparison has shown that one-and two-beam systems provide essentially identical detection limits (17). A two-beam system is required with pulsed lasers because the laser pulse duration is much shorter than the response time of the thermal lens itself.…”
Section: Oui^cay^ectsmentioning
confidence: 99%